Ketika Suara Diharamkan: Sound Horeg dan Politik Kebisingan di Jember - Mohammad Fikri (Multikultural: Jurnal Ilmu Sosial, 2025)
Jember has long been recognized as a global carnival city through the renowned Jember Fashion Carnaval (JFC), yet its cultural landscape reveals far deeper tensions. The circulation of a notarized statement from the elected regent supporting sound horeg, despite a fatwa declaring it haram by the Indonesian Ulema Council (MUI), marks a critical juncture in symbolic struggle over public space and moral authority. This conflict is not merely about noise or religious norms, but about contested claims over aesthetics, legitimacy, and cultural recognition. Employing a critical cultural anthropology framework, the article explores how grassroots sonic expressions confront elite aesthetics and institutional morality. Sound horeg emerges as a countercultural performance that challenges dominant narratives and reclaims auditory presence. The clash between religious fatwa, political populism, and popular sound culture reveals a fragmentation of authority in defining what counts as “legitimate culture.” This article underscores the urgency of reinterpreting voice and symbol politics in contemporary local society, arguing that such cultural frictions signal a broader crisis of representation and fragile legitimacy in post-reform Indonesian democracy.